2019
DOI: 10.1039/c9ra05347f
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of shale oil recovery from Qianjiang core samples by the CO2 huff-n-puff EOR method

Abstract: CO 2 Huff-n-Puff (HnP) is an effective technique for enhancing oil recovery (EOR) that can be applied to shale oil reservoirs faced with poor natural productivity and low water injectivity. The main objective of this study is to investigate the interactions of CO 2 and formation crude oil, and evaluate the CO 2 HnP performance in shale oil reservoirs in the Qianjiang depression in China. In this study, the variation rules of oil phase behavior, viscosity, saturation pressure, and swelling factor at different C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…H-n-P core floods were performed by Adel et al in the same study community, and showed a continuing rise in recovery as pressure increased above the MMP . The CO 2 sweep amount was examined by Li et al…”
Section: Gas-eor Experimental Studiesmentioning
confidence: 97%
See 3 more Smart Citations
“…H-n-P core floods were performed by Adel et al in the same study community, and showed a continuing rise in recovery as pressure increased above the MMP . The CO 2 sweep amount was examined by Li et al…”
Section: Gas-eor Experimental Studiesmentioning
confidence: 97%
“…Using an unconfined core H-n-P apparatus, oil changes of up to 100% are possible. Many organizations have described detailed accounts in immersions in such experimental setups. ,,,,,,,, Table shows some oil recovery results obtained using various cores and core holders. Since natural gas is investigated as an injection agent for EOR in unconventional oil reservoirs, laboratory studies of natural gas effectiveness for EOR usually have the composition of natural gas (see Table ).…”
Section: Gas-eor Experimental Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies of CO2 injection in shale oil systems considered reduced conditions where the oleic phase did not contain dissolved gases, which is called dead crude oils [23][24][25] . Dead crude oil models do not capture the mechanism of gas liberation from 'live oils'.…”
Section: Introductionmentioning
confidence: 99%